The autonomy of CD8+ T cells in vitro and in vivo. - Mason, D W (1988)
Experiments have been carried out in vitro and in vivo to determine to what extent CD8+ T cells in the rat can function independently of any helper activity from CD4+ cells. We have identified the culture conditions required for the autonomous proliferation of CD8+ T cells in the rat mixed leucocyte culture (MLC) and in particular have studied both the kinetics of the response and the effect of replacing the homologous serum, used in our previous MLC experiments, with fetal calf serum (FCS). The results obtained using FCS show that, early in the MLC, CD8+ T-cells proliferate at a comparable rate to the CD4+ subset but that, within 48-72 hr, the proliferation rate of the CD8+ cells ceases to increase with time. In contrast, the proliferation of the CD4+ T cells appears to be limited only by the exhaustion of the culture medium. The results also show that the proliferative responses of both CD4+ and CD8+ T cells are inhibited in homologous serum but that it is the CD8+ subset that is more affected. When CD8+ T cells, in homologous serum, are co-cultured with irradiated CD4+ T cells the proliferative activity is increased, indicating that the helper activity of the CD4+ T cells can over-ride the inhibitory effect of the serum. In vivo we have compared the abilities of injected CD4+ and CD8+ T cells to mediate rejection of skin allografts on nude rats. Grafts were rejected more rapidly on recipients of low doses of CD4+ T cells than on rats given 200 times as many CD8+ T cells. Thoracic duct lymphocytes (TDL) obtained 5 weeks after CD8+ T-cell injection always contained a population of CD4+ T cells, even when the injected CD8+ T-cell inoculum contained less than 0.1% CD4+ cells as contaminants. Evidence was obtained that these CD4+ T cells found in TDL displayed alloreactivity in MLC. Further, the intentional injection of very low doses of CD4+ cells led, after 5 weeks, to frequencies of CD4+ T cells, in thoracic duct lymph, equal to that obtained by the injection of 200 times as many cells of the same phenotype. It appears that, in T-cell-deficient rats, CD4+ cells can expand over 2000 times in a few weeks. Such expansion may explain the relatively slow rejection of skin allografts observed in these experiments when nude rats were injected with putatively pure populations of CD8+ T cells.(ABSTRACT TRUNCATED AT 400 WORDS)